TINJAUAN HUKUM ISLAM TERHADAP KEWAJIBAN PEGAWAI NEGERI SIPIL MEMBERI NAFKAH KEPADA BEKAS ISTERI PASCA PERCERAIAN (STUDI ANALISIS TERHADAP PASAL 8 PP NO. 10 TH. 1983 JO. PP. NO.45 TH.1990) - Nilkhairi Nilkhairi (Qiyas : Jurnal Hukum Islam dan Peradilan, 2017)
The formulation of this research is: Firstly, how  does  Islamic  law  manage the  livelihood  obligation  given by a husband to ex-post-divorce wife? Second, how the review of Islamic law against article 8 of Government Regulation  no. 10Year 1983 Jo. PP no. 45 of 1990 on the obligation of Civil Servants to provide for the former post-divorce wives? The method used  is qualitative  decriptive,  with normative juridical approach. This study concludes that: First, Islamic Law regulates the obligation of a husband’s livelihood to ex-wife after the divorce of mut’ah that is giving entertainment to his ex-wife and giving iddah livelihood is the livelihood given by the former husband to the ex-wife during the former wife run the iddah period  in talak raji. Both obligations are tailored to the ability of ex-husbands and the level of propriety prevailing in society so as not to burden the burden of ex-husband. There is no obligation  to provide more  for the former husband after the ex-wife past the iddah period. Second, the obligation of the former civil servant’s husband to give 1/3 of his salary after divorce to his ex-wife until the former wife is remarried, as regulated in Article 8 PP Number  10 of 1983 jo PP No. 45 of 1990 contrary to and contrary to the provisions of Islamic Law because in Islam the obligation of the former husband to give a living to the former wife only in the iddah period  because it is the provision of 1/3 salary to the former wife until the former wife married again will cause mudharat both for the former husband himself and the former family of the former husband.